Smart AcuGlove: A Mobile-Controlled Wearable for Targeted Pain Relief and Wellness - Dr. Rajalaxmi S; Shamna A. S; Kishore Kumar T. M (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The Smart AcuGlove is an embedded therapeutic device designed to automate acupressure treatment by merging electromechanical actuation with principles of Traditional Chinese Medicine (TCM). It features eight micro servo motors embedded in a flexible textile glove, each aligned with specific palmar meridian acupoints. An ESP32-based control unit orchestrates these actuators using real-time task scheduling to execute predefined stimulation protocols with precise timing and force parameters. The system is powered by a compact 12V lithium polymer battery, with voltage regulation provided by a high-efficiency DC-DC buck converter to ensure the safe operation of the actuators. The glove’s ergonomic and compliant design maintains natural hand mobility while delivering consistent therapeutic output. By eliminating the need for sensors, the Smart AcuGlove reduces system complexity enhances reliability, and minimizes operational overhead. This integration of traditional therapeutic practices with modern embedded technology offers a portable, autonomous, and repeatable solution for pain management and neuromuscular rehabilitation.